2015
DOI: 10.1103/physrevb.92.174307
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effective anisotropy: Asymptotics, simulations, and microwave experiments with dielectric fibers

Abstract: We investigate dynamic effective anisotropy in photonic crystals (PCs) through a combination of an effective medium theory, which is a high-frequency homogenisation (HFH) method explicitly developed to operate for short-waves, numerical simulations and through microwave experiments. The HFH yields accurate prediction of the effective anisotropic properties of periodic structures when the typical wave wavelength is on the order of the array pitch, specifically we investigate a square array of pitch 2 cm consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…This should, as in the two-dimensional case [8], motivate experimental studies and motivate studies of the analogous examples in three-dimensional continuum systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should, as in the two-dimensional case [8], motivate experimental studies and motivate studies of the analogous examples in three-dimensional continuum systems.…”
Section: Discussionmentioning
confidence: 99%
“…We are also motivated by wave phenomena in structured continuum mechanics that show strong directional anisotropy when forced close to specific frequencies and this behaviour is observed in optics for photonic crystals [2,9], in microwave experiments, simulations and asymptotics involving arrays of dielectric fibres [8], and in elastic lattices and frames [12]. For two-dimensional mass-spring lattices, [22], showed strongly directional cross-like responses close to critical frequencies and more recent authors [3,31,32] have demonstrated and investigated this behaviour further with [14] connecting the strong anisotropy in these model discrete systems to the continuum observations and interpreting this in terms of a change in character of the e↵ective equations from elliptic to hyperbolic; the highly directional behaviour then being along the characteristics of the hyperbolic e↵ective equations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been recently realized that many novel features of hyperbolic metamaterials such as superlensing and enhanced spontaneous emission (Poddubny et al, 2013) could be achieved thanks to dynamic anisotropy in photonic (Ceresoli et al, 2016) and phononic crystals (Colquitt et al, 2011;Antonakakis et al, 2014b). For instance, the high-frequency homogenization theory (Craster et al, 2010) establishes a correspondence between anomalous features of dispersion curves on band diagrams with effective tensors in governing wave equations: flat band and inflection (or saddle) points lead to extremely anisotropic and indefinite effective tensors, respectively, that change the nature of the wave equations (elliptic partial differential equations can turn parabolic or hyperbolic depending upon effective tensors).…”
Section: Introductionmentioning
confidence: 99%
“…The elastic waves carry the heat (phonons). It is worth remarking that, subsequent to pioneering work by Bensoussan, Lions, and Papanicolaou in Chapter 4 of their book [14], there has been a resurgence of interest in Foreword xvii high-frequency homogenization at stationary points in the dispersion diagram, which may be local minima or maxima, or even saddle points [15][16][17][18][19][20][21]. The wave is a modulated Bloch wave and modulation satisfies appropriate effective equations.…”
Section: To Ananya and Krishna To Alaa And Ismailmentioning
confidence: 99%